Development of a cell viability assay to assess drug metabolite structure–toxicity relationships. Issue 16 (15th August 2016) - Rana, Payal; Will, Yvonne; Nadanaciva, Sashi; Jones, Lyn H.
Graphical abstract: Abstract: Many adverse drug reactions are caused by the cytochrome P450 (CYP)-dependent activation of drugs into reactive metabolites. In order to reduce attrition due to metabolism-induced toxicity and to improve the safety of drug candidates, we developed a simple cell viability assay by combining a bioactivation system (human CYP3A4, CYP2D6 and CYP2C9) with Hep3B cells. We screened a series of drugs to explore structural motifs that may be responsible for CYP450-dependent activation caused by reactive metabolite formation, which highlighted specific liabilities regarding certain phenols and anilines.